MOTIVASI ISLAM DAN MOTIVASI PROSOSIAL PADA LEMBAGA AMIL ZAKAT (Studi Terhadap Para Pegawai Post Keadilan Peduli Ummat (PKPU) Cabang Semarang) - Iqbal Noor, Muhammad; Suharnomo, Suharnomo (Diponegoro Journal of Management, 2012)
Amyl is an important part of PKPU Cabang Semarang as Non-Governmental Organizations (NGOs).The role of PKPU to collect dan distribute zakat is not easy, and it takes a professional amyl. Therefore, it is necessary to know about amyl motives. The aim of this research is for identify the intrinsic motivation that influences motivation of PKPU Officials as an amyl. The other purposes of this research also to know whether there are Islamic and prosocial motivation on the PKPU cabang Semarang officials self. This research uses qualitative method where the process of collecting data is conducted with interview, so it can discovers more about amyl PKPU Cabang Semarang profession. The object in this research is PKPU officials who have passed minimum two years working period. The result of this research explain that work motivation of PKPU official influenced by work values, individual attitudes, personal desires and expectations, fatigue and work boredom and individual ability. In this research also found that there are form of Islamic and prosocial motivation on the PKPU officials